STUDI PRODUK PERALATAN PENUNJANG PETUGAS PEMADAM KEBAKARAN (STUDI KASUS: ALAT PEMADAM API RINGAN) - Toto Hendro Susilo (Universitas Mercu Buana, 2020)
This research discusses about the equipment supporting the firefighters in carrying out the flames beginning, as we know many supporting equipment used by firefighters, but not all of them are used in the process of extinguishing the beginning there was some equipment that is usually used as personal protective equipment and fire extinguisher the following operational motors as a means of transport, described here in used fire extinguisher effectiveness of the design is capable of supporting the officer where it is considered in terms of ergonomic whether it has been quite effective in its use. Due to the heavy load on lightly fire extinguisher is not enough then there will be a lot of raises new problems will be face it by officers in carrying out the flames. This research discusses about the equipment supporting the firefighters in carrying out the flames beginning, as we know many supporting equipment used by firefighters, but not all of them are used in the process of extinguishing the beginning there was some equipment that is usually used as personal protective equipment and fire extinguisher the following operational motors as a means of transport, described here in used fire extinguisher effectiveness of the design is capable of supporting the officer where it is considered in terms of ergonomic whether it has been quite effective in its use. Due to the heavy load on lightly fire extinguisher is not enough then there will be a lot of raises new problems will be face it by officers in carrying out the flames.